Thyroid dysfunction in patients with diabetes mellitus at Puducherry, India: a retrospective study - Hussain, K. Shaik Anwar (International Journal of Advances in Medicine, 2018)
Background: There is a complex interrelationship in the co-existence of thyroid dysfunction among diabetic patients and may be related to the development of cardiovascular diseases and other complications of long term metabolic derangements. The prevalence of thyroid dysfunction varies from 10 to 24% among diabetic patients. The objective of the present study was to determine the prevalence of thyroid dysfunction among the patients with diabetes mellitus in a tertiary care hospital at Puducherry, India. Methods: This retrospective study was conducted during June 2018 analysing the records of diabetes patients attending to the diabetes OPD, Department of General Medicine in the past one year and their association with thyroid dysfunction was studied. Results: Among the study participants (n=200), 14.5% (n=29) were Type I diabetics and 85.5% (n=171) were type II Diabetes patients. The prevalence of Thyroid Dysfunction (TD) among the study participants was 28.5% (n=57). The proportion of TD was higher among type 1 DM compared to type 2 (p<0.001). The prevalence of subclinical hypothyroidism was more (n=7, 24.1%) among type 1DM compared to type II DM patients (p=0.05). Conclusions: There was a higher prevalence of TD among the diabetics. TD was more frequent among type 1 DM compared to Type 2 DM patients and the most frequent TD associated with diabetes was subclinical hypothyroidism.